2012
DOI: 10.1186/1479-5868-9-88
|View full text |Cite
|
Sign up to set email alerts
|

Home environment relationships with children’s physical activity, sedentary time, and screen time by socioeconomic status

Abstract: BackgroundChildren in households of lower socioeconomic status (SES) are more likely to be overweight/obese. We aimed to determine if home physical activity (PA) environments differed by SES and to explore home environment mediators of the relation of family SES to children’s PA and sedentary behavior.MethodsParticipants were 715 children aged 6 to 11 from the Neighborhood Impact on Kids (NIK) Study. Household SES was examined using highest educational attainment and income. Home environment was measured by pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

29
297
4
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 338 publications
(333 citation statements)
references
References 32 publications
29
297
4
3
Order By: Relevance
“…lack of physical activity opportunities and unsafe playgrounds in low SES (de Vet, de Ridder, & de Wit, 2011;Evans & Kantrowitz, 2002) and home environments. Children from lower SES have greater media access, but lower access to portable play equipment (Tandon et al, 2012). Barnett at al.…”
Section: Discussionmentioning
confidence: 99%
“…lack of physical activity opportunities and unsafe playgrounds in low SES (de Vet, de Ridder, & de Wit, 2011;Evans & Kantrowitz, 2002) and home environments. Children from lower SES have greater media access, but lower access to portable play equipment (Tandon et al, 2012). Barnett at al.…”
Section: Discussionmentioning
confidence: 99%
“…One limitation is the high SES of the participants, which may limit the generalizability of results, although low SES has been shown to D r a f t associate with more screen time but not lower physical activity (Tandon et al 2012). The relative racial homogeneity of our sample may also limit the study results to similar racial groups, but it was representative of background population where the study was conducted (Statscan 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that parents play a central role in their children's screen viewing and that the time that children spend in screen viewing is influenced by both environmental (e.g. media availability in bedrooms) and socio-cultural factors (57)(58)(59) .…”
Section: Television Viewingmentioning
confidence: 99%